Exogenous spermidine improved drought tolerance in Ilex verticillata seedlings - Xie, Xiaoting; Gu, Yujie; Wang, Weili; Abbas, Farhat; Qin, Sini; Fu, Siyi; Mei, Jiaqi; Wang, Jiayan; Ma, Dexuan; Wen, Guangchao; Yang, Ying; Sharma, Anket; et al. (Frontiers in Plant Science, 2023)
Winterberry (Ilex verticillata (L.) A. Gray) is a recently introduced ornamental tree species in China that has not been closely investigated for its drought resistance. In this study, we used two-year-old cuttings from I. verticillata (L.) A. Gray and two representative varieties derived from it, I. verticillata 'Oosterwijk' and I. verticillata 'Jim Dandy', as materials to investigate how this plant responds to drought stress and whether exogenous spermidine (SPD) can alleviate the negative effects caused by drought stress. The results showed that as the degree of drought stress increased, the leaves of winterberry seedlings became chlorotic, and their edges became dry. Similarly, the relative water content, specific leaf weight, chlorophyll content, leaf nitrogen content, net photosynthetic rate, stomatal conductance and transpiration rate were significantly reduced, whereas the content of malondialdehyde continuously increased with the degree of drought stress. The activities of superoxide dismutase, peroxidase, and catalase increased under moderate drought stress and then decreased under severe drought stress. The levels of soluble sugar and abscisic acid continued to increase, while those of auxin and gibberellic acid decreased. When compared with individual drought stress, an increase in the amount of external SPD clearly alleviated the effect of drought stress on winterberry seedlings. The combined phenotypes and physiological indices of the winterberry leaves under drought stress conditions revealed that the drought resistance of the native species was significantly higher than its two varieties. This finding serves as an important theoretical foundation for the popularization and application of I. verticillata (L.) A. Gray and the two varieties.